Genetic shifts in methicillin‐resistantStaphylococcus aureusepidemic clones and toxin gene profiles in Japan: comparative analysis among pre‐epidemic, epidemic and post‐epidemic phases. Issue 3 (March 2018) - Osaka, Shunsuke; Okuzumi, Katsuko; Koide, Shota; Tamai, Kiyoko; Sato, Tomoaki; Tanimoto, Koichi; Tomita, Haruyoshi; Suzuki, Masahiro; Nagano, Yukiko; Shibayama, Keigo; Arakawa, Yoshichika; Nagano, Noriyuki
Abstract : Purpose. : The decline in methicillin‐resistant Staphylococcus aureus (MRSA) isolation rates has become a general observation worldwide, including Japan. We hypothesized that some genetic shift in MRSA might cause this phenomenon, and therefore we investigated the genetic profiles among MRSA clinical isolates obtained from three different epidemic phases in Japan. Methodology. : A total of 353 MRSA isolates were selected from 202 medical facilities in 1990 (pre‐epidemic phase), 2004 (epidemic phase) and 2016 (post‐epidemic phase). Molecular typing was performed by PCR detection of 22 genes using the polymerase chain reaction (PCR)‐based ORF typing (POT) system, including an additional eight genes including small genomic islets and seven toxin genes. Results. : Isolates with a POT1 of score 93, identified as presumed clonal complex (pCC)5‐staphylococcal cassette chromosome mec (SCC mec ) type II including ST5‐SCC mec type II New York/Japan clone, represented the major epidemic MRSA lineage in 1990 and 2004. In 2016, however, a marked decrease in isolates with a POT1 score of 93, along with changes in the epidemiology of toxin genes carried, was noted, where the carriers of tst genes including the tst‐sec combination were markedly reduced, and those possessing the seb gene alone were markedly increased. Rather, isolates with a POT1 score of 106, including pCC1 or pCC8 among the isolates with SCC mec type IV, which often links to community‐associated MRSA, were predominant. Interestingly, the pCC1 and pCC8 lineages were related to sea and tst‐sec carriage, respectively. Conclusions. : Over time, a transition in MRSA genetic profiles from a POT1 score of 93 in 1990 and 2004 to 106 in 2014 was found in Japan.